Desiring the Beautiful : The Erotic-Aesthetic Dimension of Deification in Dionysius the Areopagite and Maximus the Confessor - Ivanović, Filip, 1986- (Book collections on Project MUSE., 2019)
Desiring the Beautiful studies the concept of deification, theosis, in two of the most influential early Christian philosopher-theologians, who might be considered as theoretical consolidators of the idea of theosis, and argues that the proper understanding of their central soteriological concept must take into account its dimension of love and beauty.